Comprehensive evaluation of the prediction of fetal growth restriction using the ratio of fetal cerebellar transverse diameter to abdominal circumference combined with uterine artery blood flow parameters - Tang, Weiying; Wu, Pingping; Zheng, Yanyan; Yang, Baobao (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the value of the ratio of fetal cerebellar transverse diameter to abdominal circumference (TCD/AC) combined with uterine artery blood flow parameters in the assessment of fetal growth restriction (FGR).MethodsA retrospective analysis was conducted, including 152 women diagnosed with FGR through prenatal ultrasound screening at our hospital between January 2020 and December 2024 as the FGR group, and 156 pregnant women with normal prenatal examinations during the same period were included as the non-FGR group using a stratified sampling method. Parameters such as TCD/AC, head circumference to abdominal circumference ratio (HC/AC), and hemodynamic indicators of uterine and cerebral artery blood flow were measured through ultrasound examinations. Blood biomarkers such as insulin-like growth factor 1 (IGF-1), placental growth factor (PlGF), and vascular endothelial growth factor (VEGF) were also assessed.ResultsThere were no statistically significant differences between the two groups in terms of age, BMI, gestational weeks, parity, and gravidity (P > 0.05). The TCD/AC and HC/AC ratios in the FGR group were significantly lower than those in the non-FGR group (P < 0.05), while the uterine artery pulsatility index (PI), resistance index (RI), and systolic to diastolic peak velocity ratio (S/D) were significantly higher in the FGR group (P < 0.05). Additionally, levels of IGF-1, PlGF, and VEGF were significantly lower in the FGR group (P < 0.05). Multivariable logistic regression analysis revealed that TCD/AC, uterine artery PI (UtA-PI), uterine artery RI (UtA-RI), and uterine artery S/D (UtA-S/D) were independent predictors of FGR. Receiver operating characteristic (ROC) curve analysis demonstrated that when these indicators were used in combination, the diagnostic efficiency of FGR was improved, with an AUC of 0.820.ConclusionThe combination of TCD/AC with uterine artery blood flow parameters has high predictive value for FGR and can serve as an effective tool for early identification and management of FGR in clinical practice.